PELAKSANAAN PROGRAM KAMPUNG KELUARGA BERKUALITAS (KB) MEKAR WANGI DI KELURAHAN TANGKERANG BARAT - Rezi, Alfa (Jurnal Ilmu Administrasi Negara, 2022)
The increase in population or uncontrolled quantity dynamics can affect people’s lives in various significant aspects, one of which affects the quality of life for the function of national development, the sustainability of the advanced population or smart people and the economic conditions of the local community. This study aims to find out how the Implementation and Challenges of the Mekar Wangi Quality Family Village (KB) Program in Tangkerang Barat Village. The research method used is qualitative research using a case study approach. This research resulted in the finding that Mekar Wangsi KB Village has implemented several main programs, namely the existence of a waste bank, improving the economy through handicrafts, from health aspects such as health checks for the elderly and doing regular exercise. The obstacles in this research are the 2019 Coronavirus disease, community participation, cadre resources, and budget.